Continuous micro hard carbon network coated graphite negative electrode material and preparation method thereof

By using waste graphite materials and acid hydrogen peroxide treatment, combined with hard carbon polymer precursor and carbonization process, a continuous trace hard carbon network coated graphite negative electrode material is formed, which solves the problems of uneven hard carbon coating and short cycle life, and achieves efficient lithium ion migration and long cycle life.

CN119905560APending Publication Date: 2025-04-29LONGNAN JINTAIGE COBALT IND CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510086399.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing hard carbon coated graphite negative electrode material process has uneven and discontinuous hard carbon coating, large amount of use and obvious side effects, resulting in a short material cycle life.

Method used

Use waste graphite materials as raw materials, and are leaching through mixed solution of acid and hydrogen peroxide, impregnation of hard carbon polymer precursor solution and carbonization treatment to form a continuous trace hard carbon network coated graphite negative electrode material.

Benefits of technology

Low coating amount and continuous network hard carbon coating are achieved, which improves lithium ion migration rate and material cycle life, and reduces preparation costs and side effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905560A_ABST
    Figure CN119905560A_ABST
Patent Text Reader

Abstract

The invention discloses a continuous micro hard carbon network coated graphite negative electrode material and a preparation method thereof. The preparation method comprises the following steps: S1, adding a mixed solution of acid and hydrogen peroxide into waste negative electrode powder for leaching, washing, precipitating, removing impurities, drying, and carrying out heat treatment to obtain conductive agent loaded graphite; s2, adding the conductive agent loaded graphite in the step S1 into a hard carbon polymer precursor solution to obtain a mixed solution, and after mixing dispersion and melt dipping treatment, drying and curing to obtain graphite containing hard carbon; and S3, performing carbonization treatment on the graphite containing the hard carbon in the step S2, and performing screening and sorting to obtain the low-coating-amount continuous network hard carbon coated graphite negative electrode material. The graphite negative electrode material prepared by the method is low in coating amount, long in cycle life, high in lithium ion migration rate and simple in coating process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the fields of lithium battery negative electrode material preparation technology and waste graphite material regeneration technology, and in particular relates to a continuous trace hard carbon network coated graphite negative electrode material and a preparation method thereof. Background Art

[0002] Graphite negative electrode material is one of the important raw materials for lithium batteries, accounting for 15%-22% of the total battery mass. Currently, 80% of lithium batteries still use graphite as negative electrode material. With the continuous improvement of various performance requirements of lithium-ion batteries, the electrochemical performance requirements of graphite negative electrode materials are also gradually increasing. Therefore, graphite materials need to be further modified to improve their cycle and rate performance.

[0003] At present, the modification methods of graphite materials mainly include structural modification, surface modification, doping modification, composite treatment, coating modification, etc. Among them, surface coating treatment has little side effects and obvious performance improvement, which is a practical and effective method for performance improvement. Commonly used graphite coating materials include amorphous carbon materials, inorganic oxide materials, etc. Amorphous carbon materials include soft carbon and hard carbon, etc. This type of material has high electrolyte compatibility and stability, which can improve the rate and cycle performance of graphite. Compared with soft carbon, hard carbon has a larger interlayer spacing, higher disorder, and a larger lithium ion diffusion coefficient, which can improve the performance of graphite materials more significantly. However, the problems that still exist in the hard carbon coating modification include: the solid phase / liquid phase coating process causes the hard carbon coating layer to be uneven, discontinuous, easy to agglomerate, and agglomerate, and the actual effect is not good; the hard carbon coating is used in large quantities, which has certain side effects on the first effect of the material, resulting in poor long cycle life; the gas phase coating technology has a high threshold, the control system is complex, and the technology maturity is low. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a continuous trace hard carbon network coated graphite negative electrode material and a preparation method thereof. The present invention uses waste graphite material as raw material, and the graphite negative electrode material formed by coating treatment has a low coating amount, a long cycle life, a fast lithium ion migration rate, and a simple coating process.

[0005] The technical solution of the present invention is as follows:

[0006] The first aspect of the present invention provides a method for preparing a continuous trace hard carbon network coated graphite negative electrode material, comprising the following steps:

[0007] S1: adding a mixed solution of acid and hydrogen peroxide to the waste negative electrode powder for leaching, washing the precipitate to remove impurities, drying, and heat-treating to obtain graphite loaded with a conductive agent;

[0008] S2: adding the graphite loaded with the conductive agent in step S1 to the hard carbon polymer precursor solution to obtain a mixed solution, and after mixed dispersion and melt impregnation treatment, drying and solidifying, obtaining graphite containing hard carbon;

[0009] S3: After the hard carbon-containing graphite in step S2 is carbonized, it is screened and sorted to obtain a low-coating, continuous network hard carbon-coated graphite negative electrode material.

[0010] Preferably, in step S1, the waste negative electrode powder is a mixture containing graphite obtained by crushing and sorting the negative electrode sheets of waste batteries; the waste negative electrode powder also includes a conductive agent; and the conductive agent is carbon black.

[0011] Preferably, in step S1, the acid includes at least one of sulfuric acid and hydrochloric acid; the pH of the acid is less than 1; and the mass volume ratio of the waste negative electrode powder to the mixed solution is 1-2g:5mL.

[0012] Preferably, in step S1, the leaching time is 2-3 hours, the drying temperature is 80-100°C, and the time is 5-8 hours; the heat treatment temperature is 800-1000°C, and the time is 2-4 hours.

[0013] Preferably, in step S1, the heat treatment is performed under a nitrogen atmosphere.

[0014] Preferably, in step S2, the hard carbon polymer precursor solution is obtained by dissolving a hard carbon polymer precursor in a solvent; the hard carbon polymer precursor includes one or more of phenolic resin, furfural resin, epoxy resin, furan resin, polyvinyl alcohol, and polyacrylonitrile; and the solvent includes at least one of water, ethanol, acetone, kerosene, and dimethylformamide.

[0015] Preferably, in step S2, the solid content of the mixed solution is 40-60%, and the mass ratio of the hard carbon polymer precursor to the graphite supported by the conductive agent is 1-5:100.

[0016] Preferably, in step S3, the carbonization temperature is 1100-1500°C, the time is 2-4h, and the carbonization heating rate is 1-3°C / min.

[0017] The second aspect of the present invention provides a method for preparing a graphite negative electrode material using the preparation method described in the first aspect, wherein the surface of the graphite negative electrode material is coated with a continuous hard carbon network.

[0018] Preferably, the coating amount of the hard carbon network is 0.5-1.5%.

[0019] The beneficial technical effects of the present invention are:

[0020] (1) The present invention uses waste graphite materials as raw materials and synthesizes graphite materials with excellent performance through coating treatment, and the preparation cost is low.

[0021] (2) The present invention forms a continuous networked hard carbon coating on the surface of the material. Since the hard carbon has a higher lithium insertion potential and a larger interlayer spacing, the lithium ion migration rate is faster, and the coating is beneficial to the transmission of lithium ions. In addition, the networked coating can guide the lithium ions to transfer to the end face of the graphite matrix, thereby improving the interfacial ion conductivity of the material. The formed coating structure can alleviate the volume expansion of the material during the cycle, prevent the material from peeling off and breaking, and can improve the cycle life of the material, showing more excellent comprehensive performance.

[0022] (3) The method of the present invention has a low coating amount and small side effects; the coating process is simple, easy to operate, and has strong applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the hard carbon-coated graphite material of the present invention. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0025] The existing hard carbon coating uses solid phase / liquid phase coating, which results in uneven, discontinuous, and agglomerated hard carbon coating layers. In addition, the amount of hard carbon coating used is large, which reduces the initial effect of the material and reduces the long cycle life. In addition, the gas phase coating has high requirements and is difficult to operate. Based on this, the first aspect of the present invention protects a method for preparing a continuous trace hard carbon network coated graphite negative electrode material, comprising the following steps:

[0026] S1: adding a mixed solution of acid and hydrogen peroxide to the waste negative electrode powder for leaching, washing the precipitate to remove impurities, drying, and heat-treating to obtain graphite loaded with a conductive agent;

[0027] S2: adding the graphite loaded with the conductive agent in step S1 to the hard carbon polymer precursor solution to obtain a mixed solution, and after mixed dispersion and melt impregnation treatment, drying and solidifying to obtain graphite containing hard carbon;

[0028] S3: After the hard carbon-containing graphite in step S2 is carbonized, it is screened and sorted to obtain a low-coating, continuous network hard carbon-coated graphite negative electrode material.

[0029] It can be understood that in step S1, the waste negative electrode powder is a mixture containing graphite obtained by crushing and sorting the negative electrode sheets obtained by disassembling and sorting waste batteries, or the negative electrode sheets scrapped in the battery manufacturing process; the waste negative electrode powder includes graphite, a conductive agent, a binder, and metal impurities; the conductive agent is carbon black, and the binder includes one or more of sodium hydroxymethyl cellulose and styrene-butadiene rubber; the metal impurities include at least one of Cu, Fe, Ni, and Al.

[0030] In some embodiments of the present invention, the waste battery includes but is not limited to at least one of a ternary battery, a lithium iron phosphate battery, and a lithium manganese oxide battery. The present invention obtains waste negative electrode powder containing graphite, a conductive agent, a binder and metal impurities by conventional treatment of waste batteries, and the powder can be further used to prepare a hard carbon-coated graphite negative electrode material to avoid waste of resources.

[0031] In some embodiments of the present invention, in step S1, the acid includes at least one of sulfuric acid and hydrochloric acid; the pH of the acid is less than 1; the mass fraction of the hydrogen peroxide in the waste negative electrode powder is 5-10%, including but not limited to 5%, 6%, 7%, 8%, 9%, 10%; the mass volume ratio of the waste negative electrode powder to the mixed solution is 1-2g:5mL, including but not limited to 1g:5mL, 1.2g:5mL, 1.5g:5mL, 2g:5mL.

[0032] In some embodiments of the present invention, in step S1, the pH of the acid needs to be less than 1.

[0033] In some embodiments of the present invention, in step S1, the leaching time is 2-3 hours, including but not limited to 2 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.6 hours, 2.8 hours, and 3 hours.

[0034] In some embodiments of the present invention, in step S1, the drying temperature is 80-100°C, including but not limited to 80°C, 82°C, 85°C, 90°C, 92°C, 95°C, 100°C, and the time is 5-8h, including but not limited to 5h, 6h, 7h, 8h; the heat treatment temperature is 800-1000°C, including but not limited to 800°C, 850°C, 900°C, 950°C, 1000°C, and the time is 2-4h, including but not limited to 2h, 3h, 4h.

[0035] In some embodiments of the present invention, in step S1, the heat treatment is performed under a nitrogen atmosphere.

[0036] It can be understood that the present invention removes metal impurities and binders in the powder by leaching and removing impurities, drying, and nitrogen heat treatment of the recovered negative electrode material containing components such as conductive agent and graphite, and the conductive agent particles are uniformly and continuously loaded on the graphite surface.

[0037] In some embodiments of the present invention, in step S2, the hard carbon polymer precursor solution is obtained by dissolving a hard carbon polymer precursor in a solvent; the hard carbon polymer precursor includes one or more of phenolic resin, furfural resin, epoxy resin, furan resin, polyvinyl alcohol, and polyacrylonitrile; and the solvent includes at least one of water, ethanol, acetone, kerosene, and dimethylformamide.

[0038] In some embodiments of the present invention, in step S2, the solid content of the mixed solution is 40-60%, including but not limited to 40%, 45%, 50%, 55%, and 60%, and the mass ratio of the hard carbon polymer precursor to the conductive agent-loaded graphite is 1-5:100, including but not limited to 1:100, 2:100, 3:100, 4:100, and 5:100.

[0039] It can be understood that in step S2, the graphite with a conductive agent loaded on its surface is mixed, dispersed and fused with a hard carbon polymer precursor solution for impregnation treatment, so that the polymer material follows the solvent and penetrates into the carbon black pores on the graphite surface through capillary action, thereby improving the coating effect and making the hard carbon more evenly loaded on the graphite surface under the premise of low coating amount.

[0040] It is understood that in the present invention, the carbonization amount of the hard carbon polymer material needs to be controlled at 0.5-1.5%, including but not limited to 0.5%, 1.0%, 1.2%, 1.5%. Too much coating will lead to material adhesion and agglomeration and increase side effects, and too little coating will lead to poor effects. Among them, the carbonization amount is equal to the amount of resin added * carbonization rate. In the present invention, the carbonization rate is 30-50%.

[0041] In some embodiments of the present invention, in step S2, the drying temperature is 80-100°C, including but not limited to 80°C, 82°C, 85°C, 90°C, 92°C, 95°C, and 100°C, and the curing temperature is 130-160°C, including but not limited to 130°C, 140°C, 150°C, and 160°C.

[0042] In some embodiments of the present invention, in step S3, the carbonization temperature is 1100-1500°C, including but not limited to 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, the time is 2-4h, including but not limited to 2h, 3h, 4h, and the carbonization heating rate is 1-3°C / min. Including but not limited to 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min.

[0043] It can be understood that the hard carbon-containing graphite obtained in step S2 is directly carbonized at high temperature, and the polymer material is independently carbonized at high temperature while being connected to each other on the graphite surface, which not only avoids the adhesion and agglomeration between the particles, but also forms a continuous network coating layer on the surface of the graphite material; at the same time, since the average particle size of carbon black is about 40nm, the thickness of the hard carbon formed by carbon black is also about 40nm, which will not cause excessive coating and coating cohesion.

[0044] The second aspect of the present invention provides a graphite negative electrode material prepared by the preparation method described in the first aspect, such as Figure 1 As shown, the surface of the graphite negative electrode material is coated with a continuous hard carbon network.

[0045] In some embodiments of the present invention, the coating amount of the hard carbon network is 0.5-1.5%.

[0046] The present invention is further described below with reference to the embodiments.

[0047] Example 1

[0048] The continuous trace hard carbon network coated graphite negative electrode material is prepared as follows:

[0049] (1) 1 kg of recycled waste lithium battery graphite material was leached in 4L 1mol / L sulfuric acid and 151mL hydrogen peroxide solution for 2.5 hours, washed and impurities removed, then dried at 80°C, and heat treated at 900°C for 3 hours under a nitrogen atmosphere to obtain a purified graphite material with carbon black uniformly loaded on the surface. The waste lithium battery graphite material contains conductive agent carbon black, graphite, etc.

[0050] (2) The purified graphite material with uniformly loaded carbon black on the surface obtained in step (1) is stirred and mixed with a phenolic resin-ethanol solution, and the overall solid content is controlled to be 50%, the phenolic resin accounts for 1.6wt% of the mass of the graphite, and the phenolic resin is impregnated into the carbon black gaps on the graphite surface under stirring and mixing, followed by drying at 80°C and curing at 150°C to obtain graphite containing hard carbon.

[0051] (3) The hard carbon-containing graphite obtained in step (2) is carbonized at 1100° C. for 2 h in a nitrogen atmosphere with a heating rate of 1° C. / min. After the carbonization, the graphite is sieved through a 300-mesh sieve to obtain a hard carbon-coated graphite material, wherein the coating amount of the hard carbon network is about 0.51%.

[0052] Example 2

[0053] The continuous trace hard carbon network coated graphite negative electrode material is prepared as follows:

[0054] (1) 1 kg of recycled waste lithium battery graphite material was leached in 4 L of 1 mol / L nitric acid and 151 mL of hydrogen peroxide solution for 2.5 h, washed and impurities removed, then dried at 100 ° C, and heat treated at 800 ° C for 4 h in a nitrogen atmosphere to obtain a purified graphite material with carbon black uniformly loaded on the surface. The waste lithium battery graphite material contains conductive agent carbon black, graphite, etc.

[0055] (2) The purified graphite material with uniformly loaded carbon black on the surface obtained in step (1) is stirred and mixed with an epoxy resin-acetone solution, and the overall solid content is controlled to be 50%, and the epoxy resin accounts for 5.4wt% of the mass of the graphite. The epoxy resin is impregnated into the carbon black gaps on the graphite surface under stirring and mixing, and then thoroughly dried at 100°C and cured at 180°C to obtain graphite containing hard carbon.

[0056] (3) The hard carbon-containing graphite obtained in step (2) is carbonized at 1500° C. for 2 h in a nitrogen atmosphere with a heating rate of 3° C. / min. After the carbonization, the graphite is sieved through a 300-mesh sieve to obtain a hard carbon-coated graphite material, wherein the coating amount of the hard carbon network is about 1.5%.

[0057] Example 3

[0058] The continuous trace hard carbon network coated graphite negative electrode material is prepared as follows:

[0059] (1) 1 kg of recycled waste lithium battery graphite material was leached in 4 L of 1 mol / L sulfuric acid and 151 mL of hydrogen peroxide solution for 2.5 h, washed and impurities removed, then dried at 90 ° C, and heat treated at 1000 ° C for 2 h in a nitrogen atmosphere to obtain a purified graphite material with carbon black uniformly loaded on the surface. The waste lithium battery graphite material contains conductive agent carbon black, graphite, etc.

[0060] (2) The purified graphite material with uniformly loaded carbon black on the surface obtained in step (1) is stirred and mixed with a polyacrylonitrile-DMF solution, and the overall solid content is controlled to be 45%, and the polyacrylonitrile accounts for 3.9wt% of the mass of the graphite. The polyacrylonitrile is immersed in the carbon black gaps on the graphite surface under stirring and mixing, and then thoroughly dried at 120°C to remove the acetone solvent to obtain graphite containing hard carbon.

[0061] (3) The hard carbon-containing graphite obtained in step (2) is carbonized at 1300° C. for 3 h in a nitrogen atmosphere with a heating rate of 2° C. / min. After the carbonization, the graphite is sieved through a 300-mesh sieve to obtain a hard carbon-coated graphite material, wherein the coating amount of the hard carbon network is about 1.15%.

[0062] Example 4

[0063] The continuous trace hard carbon network coated graphite negative electrode material is prepared as follows:

[0064] (1) 1 kg of recycled waste lithium battery graphite material was leached in 4.849 L 1 mol / L sulfuric acid and 151 mL hydrogen peroxide solution for 2 h, washed and impurities removed, then dried at 90 ° C, and heat treated at 800 ° C for 4 h under a nitrogen atmosphere to obtain a purified graphite material with carbon black uniformly loaded on the surface. The waste lithium battery graphite material contains conductive agent carbon black, graphite, etc.

[0065] (2) The purified graphite material with uniformly loaded carbon black on the surface obtained in step (1) is stirred and mixed with a phenolic resin-ethanol solution, and the overall solid content is controlled to be 40%, the phenolic resin accounts for 1.0wt% of the mass of the graphite, and the phenolic resin is impregnated into the carbon black gaps on the graphite surface under stirring and mixing, followed by drying at 90°C and curing at 160°C to obtain graphite containing hard carbon.

[0066] (3) The hard carbon-containing graphite obtained in step (2) is carbonized at 1200° C. for 4 h in a nitrogen atmosphere with a heating rate of 2° C. / min. After the carbonization, the graphite is sieved with a 300-mesh sieve to obtain a hard carbon-coated graphite material.

[0067] Example 5

[0068] The continuous trace hard carbon network coated graphite negative electrode material is prepared as follows:

[0069] (1) 2 kg of recycled waste lithium battery graphite material was leached in 4.849 L 1 mol / L sulfuric acid and 151 mL hydrogen peroxide solution for 3 h, washed and impurities removed, then dried at 100 ° C, and heat treated at 1000 ° C for 2 h in a nitrogen atmosphere to obtain a purified graphite material with carbon black uniformly loaded on the surface. The waste lithium battery graphite material contains conductive agent carbon black, graphite, etc.

[0070] (2) The purified graphite material with uniformly loaded carbon black on the surface obtained in step (1) is stirred and mixed with a phenolic resin-ethanol solution, and the overall solid content is controlled to be 60%, the phenolic resin accounts for 5wt% of the mass of the graphite, and the phenolic resin is impregnated into the carbon black gaps on the graphite surface under stirring and mixing, followed by drying at 100°C and curing at 130°C to obtain graphite containing hard carbon.

[0071] (3) The hard carbon-containing graphite obtained in step (2) was carbonized at 1500° C. for 3 h in a nitrogen atmosphere with a heating rate of 3° C. / min. After carbonization, the graphite was sieved with a 300-mesh sieve to obtain a hard carbon-coated graphite material.

[0072] Comparative Example 1

[0073] Graphite negative electrode material, the preparation method thereof is as follows:

[0074] (1) Uncoated commercial graphite is used as a base material, and is stirred and mixed with a phenolic resin-ethanol solution, with a solid content of 50%, in which the phenolic resin accounts for 1.6wt% of the mass of the graphite. After being mixed evenly, the mixture is thoroughly dried at 80°C and cured at 150°C.

[0075] (2) The material obtained in step (1) was carbonized at 1100° C. for 2 h in a nitrogen atmosphere with a heating rate of 1° C. / min. After the carbonization, the material was air flow crushed and sorted, and sieved with a 300-mesh screen to obtain a hard carbon-coated graphite material, wherein the coating amount of the hard carbon network coating was about 0.51%.

[0076] Comparative Example 2

[0077] Graphite negative electrode material, the preparation method thereof is as follows:

[0078] (1) Uncoated commercial graphite is used as a base material, and is stirred and mixed with a phenolic resin-ethanol solution to control the solid content to 50%, with the phenolic resin accounting for 3.2wt% of the mass of the graphite. After being mixed evenly, the mixture is thoroughly dried at 80°C and cured at 150°C.

[0079] (2) The material obtained in step (1) was carbonized at 1100° C. for 2 h in a nitrogen atmosphere with a heating rate of 1° C. / min. After the carbonization, the material was air flow crushed and sorted, and sieved with a 300-mesh screen to obtain a hard carbon-coated graphite material, wherein the coating amount of the hard carbon network coating was about 1.02%.

[0080] Comparative Example 3

[0081] Graphite negative electrode material, the preparation method thereof is as follows:

[0082] (1) The recycled waste lithium battery graphite material is leached in 1 mol / L sulfuric acid and an appropriate amount of hydrogen peroxide solution, washed to remove impurities, then dried at 80°C, and heat treated at 900°C for 3 h in a nitrogen atmosphere to obtain a purified graphite material with a uniform surface load of carbon black.

[0083] (2) The material obtained in step (1) is stirred and mixed with an epoxy resin-acetone solution, the overall solid content is controlled to be 50%, the epoxy resin accounts for 6.8wt% of the mass of the graphite, and the epoxy resin is impregnated into the carbon black gaps on the graphite surface under stirring and mixing, followed by thorough drying at 100°C and curing at 180°C.

[0084] (3) The material obtained in step (2) was carbonized at 1500° C. for 2 h in a nitrogen atmosphere with a heating rate of 3° C. / min. After carbonization, the material was sieved through a 300-mesh sieve to obtain a hard carbon-coated graphite material, wherein the coating amount of the hard carbon network coating was about 1.9%.

[0085] Comparative Example 4

[0086] Graphite negative electrode material, the preparation method thereof is as follows:

[0087] (1) The recycled waste lithium battery graphite material is leached in 1 mol / L sulfuric acid and an appropriate amount of hydrogen peroxide solution, washed to remove impurities, then dried at 80°C, and heat treated at 600°C for 3 h in a nitrogen atmosphere to obtain a purified graphite material with a uniform surface load of carbon black.

[0088] (2) The material obtained in step (1) is stirred and mixed with an epoxy resin-acetone solution, the overall solid content is controlled to be 50%, the epoxy resin accounts for 5.4wt% of the mass of the graphite, and the epoxy resin is impregnated into the carbon black gaps on the graphite surface under stirring and mixing, followed by thorough drying at 100°C and curing at 180°C.

[0089] (3) The material obtained in step (2) was carbonized at 1500° C. for 2 h in a nitrogen atmosphere with a heating rate of 3° C. / min. After carbonization, the material was sieved through a 300-mesh sieve to obtain a hard carbon-coated graphite material, wherein the coating amount of the hard carbon network coating was about 1.5%.

[0090] Test example:

[0091] The graphite materials prepared in the examples and comparative examples were tested for gram capacity, initial efficiency, 3C capacity retention rate and capacity retention rate after 500 cycles. The results are shown in Table 1.

[0092] Table 1 Properties of graphite materials prepared in Examples and Comparative Examples

[0093]

[0094] As can be seen from Table 1, the 3C capacity retention rate of the graphite material prepared in the comparative example is lower than that in the embodiment, and the capacity retention rate is also significantly reduced after 500 cycles. The graphite material prepared in the present invention has better comprehensive performance.

[0095] The method of the present invention solves the problems of discontinuous hard carbon coating, large coating amount, side effects, complex hard carbon coating method and cumbersome process. The characteristics of waste graphite materials are cleverly utilized to prepare a high-rate long-cycle graphite negative electrode material with a continuous hard carbon coating structure in one step, and waste graphite materials are reused to prepare high-performance new materials.

[0096] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.

Claims

1. A method for preparing a continuous trace amount of hard carbon network coated graphite negative electrode material, characterized in that: The steps include: S1: adding a mixed solution of acid and hydrogen peroxide to the waste negative electrode powder for leaching, washing the precipitate to remove impurities, drying, and heat-treating to obtain graphite loaded with a conductive agent; S2: adding the graphite loaded with the conductive agent in step S1 to the hard carbon polymer precursor solution to obtain a mixed solution, and after mixed dispersion and melt impregnation treatment, drying and solidifying, obtaining graphite containing hard carbon; S3: After the hard carbon-containing graphite in step S2 is carbonized, it is screened and sorted to obtain a low-coating, continuous network hard carbon-coated graphite negative electrode material.

2. The preparation method according to claim 1, characterized in that: In step S1, the waste negative electrode powder is a mixture containing graphite obtained by crushing and sorting the negative electrode sheets of waste batteries; the waste negative electrode powder also includes a conductive agent; and the conductive agent is carbon black.

3. The preparation method according to claim 1, characterized in that: In step S1, the acid includes at least one of sulfuric acid and hydrochloric acid; the mass volume ratio of the waste negative electrode powder to the mixed solution is 1-2g:5mL.

4. The preparation method according to claim 1, characterized in that: In step S1, the leaching time is 2-3 hours, the drying temperature is 80-100°C; the heat treatment temperature is 800-1000°C, and the time is 2-4 hours.

5. The preparation method according to claim 1, characterized in that: In step S1, the heat treatment is performed in a nitrogen atmosphere.

6. The preparation method according to claim 1, characterized in that: In step S2, the hard carbon polymer precursor solution is obtained by dissolving a hard carbon polymer precursor in a solvent; the hard carbon polymer precursor includes one or more of phenolic resin, furfural resin, epoxy resin, furan resin, polyvinyl alcohol, and polyacrylonitrile; and the solvent includes at least one of water, ethanol, acetone, kerosene, and dimethylformamide.

7. The preparation method according to claim 1, characterized in that: In step S2, the solid content of the mixed solution is 40-60%, and the mass ratio of the hard carbon polymer precursor to the graphite supported by the conductive agent is 1-5:

100.

8. The preparation method according to claim 1, characterized in that: In step S3, the carbonization temperature is 1100-1500°C, the time is 2-4h, and the carbonization heating rate is 1-3°C / min.

9. A method for preparing a graphite negative electrode material according to any one of claims 1 to 8, characterized in that: The surface of the graphite negative electrode material is coated with a continuous hard carbon network.

10. The graphite negative electrode material according to claim 9, characterized in that: The coating amount of the hard carbon network is 0.5-1.5%.

Citation Information

Cited By

  • Spherical graphite negative electrode material with controllable morphology and preparation method thereof

    CN120767301A

  • Shape-controllable spherical graphite negative electrode material and preparation method thereof

    CN120767301B